Delayed Enrollment in Medicaid by Eligible Families with Children Admitted to the Neonatal Intensive Care Unit - Eubanks, Jessica; Tumin, Dmitry; Akpan, Uduak S. (American Journal of Perinatology, 2025)
All children, including infants admitted to the neonatal intensive care unit (NICU) require health insurance. However, despite eligibility for Medicaid, many children are uninsured due to barriers in the enrollment process. Therefore, we studied the prevalence of and reasons for delayed insurance enrollment among families with Medicaid-eligible infants admitted to the NICU.This was a single-center, prospective survey study conducted in a seventy-one-bed level IV NICU. All neonates eligible for Medicaid enrollment and hospitalized for at least 21 days were eligible for the study. The primary outcome variable was enrollment in public insurance by the time of survey completion. We also examined the reported barriers to insurance enrollment.We enrolled 102 infants in this study, 76% of whom were already enrolled in Medicaid at survey completion. Common barriers to Medicaid enrollment reported by infants' parents were difficulty understanding the application process and the Medicaid application forms.Although most Medicaid-eligible neonates in the NICU had obtained insurance coverage prior to the fourth week of life, simplifying the application process (including the application forms) can remove the remaining barriers to coverage enrollment.
Keywords: Medicaid; prematurity; underinsurance; enrollment barriers